Dynamic Monitoring Area Allocation for Aerial Post-Disaster Situation Monitoring - Zobel, Julian; Stöhr, Niklas; Kundel, Ralf; Lieser, Patrick; Steinmetz, Ralf (Electronic Communications of the EASST, 2021)
In the aftermath of a disaster, information about the location of affected civilians is very important for an efficient disaster relief. A continuously operating autonomous Aerial Monitoring System with Unmanned Aerial Vehicles (UAVs) can provide an up-to-date overview of the disaster area by tracking wireless signals from carried or worn smart devices on the ground. This work highlights that dynamic allocation of monitoring areas facilitates a continuous deployment of a resilient Aerial Monitoring System with heterogeneous UAVs.